The Impact of Climate on Surging at Donjek Glacier, Yukon, Canada - Kochtitzky, William; Winski, Dominic; McConnel, Erin; Kreutz, Karl; Campbell, Seth; Enderlin, Ellyn M.; Copland, Luke; Williamson, Scott; Main, Brittany; Dow, Christine; Jiskoot, Hester (2019)
Links between climate and glacier surges are not well understood, but are required to enable prediction of glacier surges and mitigation of associated hazards. Here, we investigate the role of snow accumulation and temperature on surge periodicity, glacier area changes, and timing of surge initiation since the 1930s for Donjek Glacier, Yukon, Canada. Snow accumulation measured in three ice cores collected at Eclipse Icefield, at the head of the glacier, indicate that a cumulative accumulation of 13.1–17.7 m w.e. of snow occurred in the 10–12 years between each of its last eight surges. This suggests that a cumulative accumulation threshold must be passed before the initiation of a surge event, although it remains unclear whether the relationship between cumulative snowfall and surging is due to the consistency in repeat surge interval and decadal average precipitation, or if it is indeed a prerequisite to surging. We also examined the 1968 to 2017 climate record from Burwash Landing, 30 km from the glacier, to determine whether a relationship exists between surge periodicity and an increase of 2.5 °C in mean annual air temperature over this period. No such relationship was found, although each of the past 8 surge events has been less extensive than the previous, with the terminus area approximately 7.96 km 2 smaller after the 2012–2014 surge event compared to the ~ 1947 surge event. This study shows that the impacts of climate and surging is not yet understood and suggests that internal glacier processes may play a more important role in controlling glacier surge events.